Genomic signature of adaptation in maize landraces (2015)
The tremendous amount of genetic diversity in landraces has been the building blocks for the sueeess in breeding maize as one the most important food resources. The extremely broad adaptability shown during maize domestication, growing in areas ranging from almost sea level to 2,800 meter highland fields, is the result of the interplay between genomie variation and natural selection. Genetie charaeterization of maize landraces does not only provide the gateway to understand important genetic factors in adaptation, but also help to uncover these under-used, yet desirable genetic variants for the anticipated agricultural and climate challenge. Using next- generation sequencing technologies, this study is aimed to understand the genomie composition of maize landraees, identify regions in the genome responsible for genetie adaptation during domestication; and, finally, to mine pre-adapted, breeding potential genes according to mega environment clasification to maize landrace accessions